DYNAMICAL INDUSTRIAL SYSTEMS - Adendorff, K. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: There is widespread evidence that industrial systems do not consistently perform in a stable fashion regardless of how diligently they have been designed and operated. Operation of a system is often in a dynamic sense chaotic or verges on the chaotic. The essence of such performance deserves analysis using the tools of chaos theory. AFRIKAANSE OPSOMMING: Daar is voldoende getuienis dat industri